HAMBATAN F&B SERVICE DALAM PENERAPAN STANDAR PELAYANAN BERNUANSA MEXICAN DI UNIQUE ROOFTOP BAR RIMBA BY AYANA BALI - Putra, Ida Bagus Putu Dhiratsaha Adi; Andiani, Nyoman Dini; Trianasari, Trianasari (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the obstacles in implementing Food and Beverage (F&B) Service training results towards Mexican-themed service standards at Unique Rooftop Bar Rimba by Ayana Bali. Using a descriptive qualitative approach through interviews, observations, and documentation with managers, supervisors, staff, and trainees, this study found that routine training has been conducted but has not been optimal in maintaining service consistency. The main obstacles include staff's lack of understanding of Mexican culture and service style, limited communication with international guests, and the difficulty of balancing five-star hotel standards with the relaxed atmosphere of a themed restaurant. To overcome these obstacles, it is recommended to adjust the training materials to suit Mexican cultural concepts, increase hands-on practice, strengthen post-training evaluations, and provide cross-cultural communication training. The results of this study are expected to support the development of international-themed F&B Service training in the Hospitality industry.